Rapidly Progressive Pericardial Effusion and Cardiac Tamponade in a Term Infant with an Umbilical Venous Catheter: A Case Report - Min-Jung Park; Ja-Hye Ahn; Hyun Ju Lee; Hyun-Kyung Park; Jae-Kyoon Hwang; Chang-Ryul Kim; Jae Yoon Na (Korean Society of Neonatology, 2022)
Pericardial effusion (PCE) in neonates has various clinical presentations depending on the amount and speed of fluid accumulation and can cause cardiac tamponade (CT). We report a case of rapidly accumulating PCE and near-fatal CT with an umbilical venous catheter successfully resolved by emergent echo-guided pericardiocentesis in a term infant who had been hospitalized with meconium aspiration syndrome and persistent pulmonary hypertension. This case report suggests that if a patient with an intracardiac umbilical catheter shows sudden cardiopulmonary instability, the possibility of PCE and CT should be considered. Furthermore, if necessary, emergency drainage of the PCE and removal of the umbilical catheter should be immediately performed.